APLIKASI EDUKASI MITIGASI DAN PELAPORAN KEJADIAN BENCANA BERBASIS ANDROID - Luthfiya Anggraini; Faisal (AGENTS: Journal of Artificial Intelligence and Data Science, 2021)
Makassar City is one of the cities in Indonesia with a high potential for disaster threats, including earthquakes, tsunamis, landslides, floods, droughts, extreme weather, epidemics, and social conflicts. Due to the geographical condition of the city of Makassar which is vulnerable to disaster threats, it requires fast and effective coordination and communication in the government sector, in this case the Regional Disaster Management Agency (BPBD) in order to take emergency response actions against disasters. This study aims to create an application that can help the community to report surrounding conditions when a disaster occurs to the Makassar City BPBD, as well as to educate the public about disaster mitigation. The type of research is an experimental method with a qualitative research approach and the design method used is the Waterfall. System testing using Blackbox and Beta is done by conducting interviews with pre-determined sources. The results of this study reveal that this application helps the community in reporting disaster events that occur around them to the Makassar City BPBD, and also educate the public in terms of disaster mitigation guidelines, and is expected to help Makassar City BPBD in handling disaster emergency response and socialization of disaster mitigation to society.